Electrochemical and spectroscopic investigation of neutral, oxidized and reduced double-decker lutetium(III) phthalocyanines - Yilmaz, I; Nakanishi, T; Gürek, A; Kadish, KM (World Scientific Publ Co Pte Ltd, 2003)
The double-decker lutetium(III) phthalocyanine [(C6H13S)(8)Pc](2)Lu was investigated by electrochemical and spectroelectrochemical methods and comparisons made to previously investigated [(C12H23S)(4)Pc](2)Lu and (Pc)(2)Lu under the some experimental conditions. All three Compounds undergo a single reversible one-electron oxidation and up to four reversible one-electron reductions in CH2Cl2 containing 0.1 M tetra-n-butylammonium perchlorate (TBAP). The octa- and tetra substituted phthalocyanine derivatives exhibit one oxidation and three or four reductions in solution while five reductions can be detected for the two compounds in a gel-like cast film membrane of tetraoctylphosphoniumn bromide (4C(8)P(+)Br(-)) at a basal plane pyrolytic graphite electrode which was immersed in aqueous 0.5 M KCl. The half-wave potentials of these SR substituted complexes in CH2Cl2 are negatively shifted by 210-490 mV from E-1/2 values for the same compounds in the aqueous 4C(8)P(+)Br(-) matrix and five reductions of these compounds are observed under the latter experimental conditions. The UV-visible spectra of the compounds were measured in five different oxidation states and ESR spectra were also characterized for the neutral and doubly reduced complexes. As was expected, [(Pc)(2)Lu](-), {((C6H13S)(8)Pc](2)Lu}(-) and {[(C12H25S)(4)Pc](2)Lu}- are silent while electrogenerated [(Pc)(2)Lu](2-) [(C6H13S)(8)Pc](2)Lu}(2-) {[(C12H25S)(4)Pc](2)Lu}(2-) show broad strong signals at g = 2.0046, 2.0041 and 2.0034 with linewidths of 13.9, 16.1 and 12.9, respectively. These signals are indicative of organic free radicals where the unpaired electrons of the dianion are delocalized over two macrocycles. Copyright (C) 2003 Society of Porphyrins & Phthalocyanines.
Symposium on Porphyrins and Supramolecular Assemblies held at the 203rd Meeting of the Electrochemical-Society -- APR 29-30, 2003 -- PARIS, FRANCE
Keywords: electrogenerated double-decker lutetium phthalocyanines; electrochemistry; spectroelectrochemistry; ESR; tetraoctylphosphonium bromide; cast films